Evaluation of the Variation in Dynamic Load Factor Throughout a Highly Skewed Steel I-Girder Bridge - Almoosi, Y.; McConnell, J.; Oukaili, N. (Engineering, Technology & Applied Science Research, 2021)
The Dynamic Load Factor (DLF) is defined as the ratio between the maximum dynamic and static responses in terms of stress, strain, deflection, reaction, etc. DLF adopted by different design codes is based on parameters such as bridge span length, traffic load models, and bridge natural frequency. During the last decades, a lot of researches have been made to study the DLF of simply supported bridges due to vehicle loading. On the other hand, fewer works have been reported on continuous bridges especially with skew supports. This paper focuses on the investigation of the DLF for a highly skewed steel I-girder bridge, namely the US13 Bridge in Delaware State, USA. Field testing under various load passes of a weighed load vehicle was used to validate full-scale three-dimensional finite element models and to evaluate the dynamic response of the bridge more thoroughly. The results are presented as a function of the static and dynamic tensile and compressive stresses and are compared to DLF code provisions. The result shows that most codes of practice are conservative in the regions of the girder that would govern the flexural design. However, the DLF sometimes exceeds the code-recommended values in the vicinity of skewed supports. The discrepancy of the DLF determined based on the stress analysis of the present study, exceeds by 13% and 16% the values determined according to AASHTO (2002) for tension and compression stresses respectively, while, in comparison to BS5400, the differences reach 6% and 8% respectively.